A Speech Act Analysis of an Interview Podcast between Siti Fadilah and Deddy Corbuzier on YouTube - Heva Rostiana; Ari Fajria Novari (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2021)
This research aimed to investigate and analyze the speech acts utterances, especially in illocutionary types happened in an interview podcast between Siti Fadilah and Deddy Corbuzier on YouTube. The research conducted a descriptive qualitative method. The data in this research was in the speech act uterances used Siti Fadilah and Dedy Corbuzier which contains elements of illocutionary speech acts. Based on the analysis result, the authors analyzed 107 data of illocutionary speech acts. In this research, the authors found 5 types of illocutionary speech acts which used in an interview podcast between Siti Fadilah and Deddy Corbuzier on YouTube. Those are; assertive, directive, commissive, expressive, and declarative. The percentage of illocutionary speech act happened in an interview podcast between Siti Fadilah and Deddy Corbuzier on YouTube: assertive (70,09%), directive (3,73%), commissive (0,9%), expressive (0,93%), and declarative (24,30%).